2012
DOI: 10.1007/7854_2012_226
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression: A Role for Hippocampal Neurogenesis?

Abstract: Since its discovery in mammals, adult neurogenesis, the process of generating functional neurons from neural progenitor cells in the adult brain, has inspired numerous animal studies. These have revealed that adult neurogenesis is a highly regulated phenomenon. Enriched environment, exercise and learning for instance, are positive regulators while stress and age are major negative regulators. Stressful life events are not only shown to reduce adult neurogenesis levels but are also discussed to be a key element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 165 publications
(224 reference statements)
3
42
0
5
Order By: Relevance
“…Neurogenesis in the hippocampus of mammals may be significantly less in depressive status than in non-depressive healthy controls, which is consistent with the findings obtained from adult humans [4950]. Neurogenesis may also be decreased in the hippocampus and apoptosis may be enhanced in cerebral cells of CMS-treated rats [30].…”
Section: Discussionsupporting
confidence: 86%
“…Neurogenesis in the hippocampus of mammals may be significantly less in depressive status than in non-depressive healthy controls, which is consistent with the findings obtained from adult humans [4950]. Neurogenesis may also be decreased in the hippocampus and apoptosis may be enhanced in cerebral cells of CMS-treated rats [30].…”
Section: Discussionsupporting
confidence: 86%
“…27 Interestingly, altered brain monoamine levels resulting from antidepressant treatment demonstrate a consistent reinforcing effect on adult hippocampal neurogenesis. 34 Consistent with this hypothesis, Samplin et al 35 found that males from a community sample with a history of EA had smaller hippocampal volumes. Childhood trauma was assessed by the same 28-item CTQ.…”
Section: Biological Implicationsmentioning
confidence: 91%
“…In humans, aberrant adult neurogenesis has been linked to epilepsy (Hattiangady et al, 2004; Jessberger et al, 2007), intellectual disability (Luo et al, 2010; Scotto-Lomassese et al, 2011), affective disorders (Samuels and Hen, 2011; Valvezan and Klein, 2012; Petrik et al, 2012; Lee et al, 2013), anxiety disorders (Revest et al, 2009), and, especially, schizophrenia (Reif et al, 2007; Toro and Deakin, 2007; Inta et al, 2011). We focus on schizophrenia, as it has been subject to the most-intensive study, and, importantly, hippocampal and olfactory function are notably compromised in schizophrenic patients, as described below.…”
Section: Potential Disadvantages Of Adult Neurogenesismentioning
confidence: 99%